The world of agritourists: A psychological perspective - Christou, Prokopis A.; Lashley, Conrad; Saveriades, Alexis (My University, 2009)
An ethnographic study conducted in order to investigate agritourist satisfaction in the Mediterranean Island of Cyprus brings to the surface novel information in regards to motivation; the formation of expectations; satisfaction achievement; and behavioural intentions, of agritourists. The findings of the study contribute to the existing body of knowledge in the field of tourism by divulging further details regarding the relatively unexplored niche market of agritourists. Further to this and perhaps more importantly, the fieldwork findings assist destinations and practitioners alike to achieve guest satisfaction and foster the positive future behavioural intentions of their guests. .
Keywords: Agritourism; Agritourists; Cyprus; Ethnography; Psychology